2004
DOI: 10.1290/1543-706x(2004)40<211:clchaa>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Cell Line Cross-Contamination: How Aware Are Mammalian Cell Culturists of the Problem and How to Monitor It?

Abstract: HeLa was the first human cell line established (1952) and became one of the most frequently used lines because of its hardiness and rapid growth rate. During the next two decades, the development of other human cell lines mushroomed. One reason for this became apparent during the 1970s, when it was demonstrated that many of these cell lines had been overgrown and replaced by fast-growing HeLa cells inadvertently introduced into the original cultures. Although the discovery of these "HeLa contaminants" prompted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2006
2006
2011
2011

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(31 citation statements)
references
References 10 publications
1
30
0
Order By: Relevance
“…Accordingly, awareness of good laboratory practices and careful vigilance with fish cell cultures as detailed by Lannan (1994) should be followed to avoid confusion of cell lines. The problem of intraspecies and interspecies cross-contamination among cell lines has been recognized for half a century, and although reviews have been published, evidence of continued use of misidentification and cellular cross-contamination of cell cultures has not declined (Buehring et al 2004).…”
Section: Cross-contamination and Over Passagementioning
confidence: 99%
“…Accordingly, awareness of good laboratory practices and careful vigilance with fish cell cultures as detailed by Lannan (1994) should be followed to avoid confusion of cell lines. The problem of intraspecies and interspecies cross-contamination among cell lines has been recognized for half a century, and although reviews have been published, evidence of continued use of misidentification and cellular cross-contamination of cell cultures has not declined (Buehring et al 2004).…”
Section: Cross-contamination and Over Passagementioning
confidence: 99%
“…The intra-species and inter-species cross-contamination represent an important problem not only due to the research articles which use misidentified cell lines with the corresponding false results (Buehring et al 2004), as well in the production of cell lines destined to clinical uses such as the stem cell lines (Borge and Evers 2003;Hyslop et al 2005). The stem cell lines are subjected to rigorous characterization and quality because in the future they will be applied to human transplant therapies (Hyslop et al 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Tissue culture was done on the open bench, with the help of a Bunsen burner to give a small window of relatively sterile air, using materials collected and prepared on an almost daily basis (Masters 2002). During the next 15 years, many human cell lines from different origin tissues were established (Buehring et al 2004). In 1968, Gartler noted that many cell lines originated from Caucasian donors have enzyme forms rare in Caucasian individuals but with 30% of frequency in people of African origin, specifically the A form of glucose-6-phosphate dehydrogenase (G6PD), found in the HeLa cells, which migrates faster in gel electrophoresis than the B form typically found in Caucasian individuals (Gartler 1968).…”
Section: Introductionmentioning
confidence: 99%
“…Their paper also includes the outcome of a PubMed database analysis which uncovered 220 research papers based on the use of cross-contaminated cell lines. Buehring et al (2004) also revealed a disturbing trend. While the number of publications in the PubMed database increased steadily from 1969 through 2004, the number of papers involving HeLa contaminants increased far more rapidly.…”
Section: Brief Historymentioning
confidence: 99%
“…Masters (2005) Buehring et al (2004) uncovered 220 publications that involved cross-contaminated cultures. A survey distributed and analyzed by Buehring et al (2004) in order to obtain a profile of active cell culture workers revealed that of the 483 respondents, 32% used HeLa cells, 9% were unwittingly using HeLa contaminants, 33% of the investigators tested for authenticity, 35% obtained their cell lines from other laboratories rather than from a major repository. Their paper also includes the outcome of a PubMed database analysis which uncovered 220 research papers based on the use of cross-contaminated cell lines.…”
Section: Brief Historymentioning
confidence: 99%